The RIFLE criteria and mortality in acute kidney injury: A systematic review - Ricci, Z.; Cruz, D.; Ronco, C. (Kidney international, 2008)
In 2004, the Acute Dialysis Quality Initiative workgroup proposed a multilevel classification system for acute kidney injury (AKI) identified by the acronym RIFLE (Risk, Injury, Failure, Loss of kidney function, and End-stage kidney disease). Several studies have been published aiming to validate and apply it in clinical practice, verifying whether outcome progressively worsened with the severity of AKI. A literature search from August 2004 to June 2007 was conducted: 24 studies in which the RIFLE classification was used to define AKI were identified. In 13 studies, patient-level data on mortality were available for Risk, Injury, and Failure patients, as well as those without AKI (non-AKI). Death was reported at ICU discharge, hospital discharge, 28, 30, 60, and 90 days. The pooled estimate of relative risk (RR) for mortality for patients with R, I, or F levels compared with non-AKI patients were analyzed. Over 71 000 patients were included in the analysis of published reports. With respect to non-AKI, there appeared to be a stepwise increase in RR for death going from Risk (RR=2.40) to Injury (RR=4.15) to Failure (6.37, P<0.0001 for all). There was significant intertrial heterogeneity as expected with the varying patient populations studied. The RIFLE classification is a simple, readily available clinical tool to classify AKI in different populations. It seems to be a good outcome predictor, with a progressive increase in mortality with worsening RIFLE class. It also suggests that even mild degrees of kidney dysfunction may have a negative impact on outcome. Further refinement of RIFLE nomenclature and classification is ongoing.